Student’s Perspectives on the Efficacy of Tandem Application in Enhancing Speaking Proficiency - Batubara, Putri Fadillah; Maslathif Dwi Purnomo (Institut Agama Islam Negeri Palopo, 2025)
This study explored students' perceptions of the effectiveness of the Tandem app in improving their English language proficiency. The results show that the use of Tandem significantly improves students' confidence, fluency and adaptability in cross-cultural communication. Direct interaction with native speakers helps students overcome their fear of making mistakes, allowing them to think and respond more naturally in English. In addition, exposure to different accents and communication styles broadens their linguistic understanding. However, challenges remain, including limited structured feedback from native speakers and technical limitations such as unstable Internet connections. Many students expressed the need for explicit grammar correction and a more structured learning environment to complement the informal learning environment of this app. Therefore, while Tandem proves to be an effective tool for language learning, its integration into formal education, especially teacher-led instruction, will optimise learning outcomes. This research highlights the potential of technology-assisted language learning, while emphasising the importance of structured feedback and pedagogical support.